In Vitro Platelet Reaction with Isolated Glomerular Basement Membrane - Ts'ao, Chung-Hsin (Thrombosis and Haemostasis, 1971)
Purified canine glomerular basement membrane (BM) induced platelet aggregation when added to heparinized platelet-rich plasma (PRP) of the rat. Platelet aggregation induced by BM suspension was compared with that induced by collagen submicroscopically. When aliquots of BM or collagen suspension of the same concentration (2 mg/ml saline) was incubated with PRP, platelet-BM reaction was far less pronounced than platelet-collagen reaction. Platelet-BM reaction was slow and aggregates were small; swelling and pseudopod formation were obvious but platelet degranulation was limited. With high concentration (5 mg/ml saline) of BM suspension, the aggregation time was shortened and aggregates were generally composed of larger number of platelets. Treatment of BM with collagenase abolished the platelet-BM reaction. It is postulated that similar “platelet aggregating” elements in collagen are present in BM; but the quantity of these elements is less in a BM than in a collagen molecule.